Exploring Emotional and Academic Struggles of Low-income Students in Nepali Public Schools - Sushila Bhusal (KMC Journal, 2026)
Students from low-income families often experience emotional and academic challenges that hinder their education participation and achievement. Despite growing evidence on the relationship between poverty and educational outcomes, little qualitative research has explored how these challenges are experienced by students in Nepali public schools. In the context of Nepali public schools, this study aimed to explore the emotional and academic struggles experienced by a student of low-economic background and examine how these experiences influence learning behavior and academic performance. Guided by Bronfenbrenner’s Ecological Systems theory, the study adopted general qualitative research design, data were collected through an in-depth interview with the purposively selected 15 years old student. The collected data were analyzed using Braun and Clarke’s six phase thematic analysis. The findings revealed four major themes; emotional stress and anxiety arising from financial hardship and family responsibilities, low self-esteem and social isolation, the influence of emotional distress on learning behavior and classroom participation, and the impact of economic hardship on academic performance through limited learning resources, excessive household responsibilities, and reduced study time. The findings demonstrate that poverty affects not only students’ access to educational resources but also their emotional well-being, motivation, concentration, and engagement in learning. The study highlights the importance of coordinated support from schools, families, communities, and policymakers to address the emotional and educational needs of economically disadvantaged learners. Strengthening counseling services, targeted financial assistance, and inclusive school practice can contribute to improving both students’ well-being and academic success in Nepali public schools.